Inquiry into the mental development of children - Sperry, Mabelle; Nellie Dorothy Hughes (My University, 1906)
Introduction: The above data were collected during investigations made in the Manhattan City Schools in the grade one to seven inclusive. Eighty-seven children were examined of which number forty-five were girls and forty-two boys. Some of the test made, such as those for color-sense and perception, require some explanation. In the former the color sense tester was used, the colors appearing being red, blue, green, white, and gray. Very little actual color blindness was found - less than one half of one per cent. In some cases remarkable color ignorance was discovered however. Gray and white were confused to a large extent but as this was noticed also among college students it is not a remarkable fact. The boys seemed to be more easily confused on this point than the girls but this was the case with regard to the other colors also. When mistakes were made blue and green were the colors oftenest confused after gray and white. In some cases yellow and green and in others yellow and red were taken for each other. A remarkable and as yet unaccountable mistake was one encountered mostly in the higher grades, namely that of calling gray, purple or lavender. In the higher grades the pupils and especially the girls persisted in seeing differences of degree in the colors - dark red, lint red, and so on - where no such differences existed. In naming the colors some of the boys in the higher grades used descriptive terms such as dirty white, smoke color, water color, etc. Only ten out of the eighty-seven made no mistakes. Mile the ignorance of color shown in these investigations is not very extensive the standard could undoubtedly be raised by a systematic teaching of color and such teaching should form a part of the work given in the grades. In testing for perception a list of words was given and the children asked to pick out those containing the letter (e) in the shortest time possible.
Citation: Sperry, Mabelle and Nellie Dorothy Hughes. Inquiry into the mental development of children. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Psychology; Mental Development; Children; Theses